Investigation Of Surface Properties For Self-Cleaning Coating On Ceramic Wall Tiles - Khor, Jia Yen (2019)
This study emphasized on the surface properties of Cu doped TiO2 coated ceramic wall tiles in producing self-cleaning and antibacterial coating properties. Cu doped TiO2 powder was synthesized via hydrothermal method followed by calcination at 300 ºC. The phase transformation from tetragonal structure of pure TiO2 to hexagonal TiO2 was shown in X-ray diffraction (XRD) result, followed by morphology transformation from near-spherical shape to nanotubes as evidenced in Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) micrographs. The incorporation of Cu2+ metal ion dopant into TiO2 was proved in reducing the band gap energy of TiO2 from 3.2 eV to 2.07 eV. Also, Cu doped TiO2 exhibited greater photocatalytic degradation than undoped TiO2. Next, PVA/GA was found to have better coating adhesion due to the role of glutaraldehyde (GA) as polymer chains crosslinking agent. Five coating layers were determined as the appropriate coating cycles on ceramic wall tiles due to the factors of physical appearance, powder concentration and surface roughness. The surface properties of the coated ceramic wall tiles (glazed and unglazed) by different coating techniques (dip coating and spray coating) were investigated in functionality characterizations. Spray coated tiles displayed homogeneous coating surface compared to dip coated tiles. In pencil hardness test, spray coated unglazed tiles has the highest scratch resistance. In solution immersion test, both dip and spray coated tiles experienced coating peeled off in acid (pH 4) and immersion, but no peeled off surface was seen when immersed in water (pH 7) and alkaline (pH 9) solution.